2017
DOI: 10.2147/idr.s147272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new automated Abbott RealTime MTB RIF/INH assay for qualitative detection of rifampicin/isoniazid resistance in pulmonary and extra-pulmonary clinical samples of <em>Mycobacterium tuberculosis</em>

Abstract: A new automated real-time PCR assay for the detection of rifampicin (RIF) and isoniazid (INH) resistance in Mycobacterium tuberculosis (MTB) was evaluated. A total of 163 clinical samples (128 pulmonary and 35 extra-pulmonary) were processed using four PCR assay kits: Abbott RealTime MTB RIF/INH, Genotype MTBDRplus, Xpert/MTB RIF, and Anyplex MTB/MDR. The results of phenotypic drug-susceptibility testing using BACTECMGIT 960 were used as reference. The sensitivity and specificity of the new Abbott RealTime MTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…But in 3/19 INH resistance specimens, mutation(s) was not detected with the Abbott RealTime MTB RIF/INH assay resulting with 84.2% sensitivity. This proportion is relatively similar to the study conducted by Ruiz P et al (78.8%) [ 20 ] and Tam KK et al (84%) [ 21 ]. Discordant INH resistance pattern between DST and this assay could be as a result of INH resistance is linked with multiple genes and appears more complex [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…But in 3/19 INH resistance specimens, mutation(s) was not detected with the Abbott RealTime MTB RIF/INH assay resulting with 84.2% sensitivity. This proportion is relatively similar to the study conducted by Ruiz P et al (78.8%) [ 20 ] and Tam KK et al (84%) [ 21 ]. Discordant INH resistance pattern between DST and this assay could be as a result of INH resistance is linked with multiple genes and appears more complex [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…A misdiagnosis for Rif on the RT MTB RIF/INH assay has also been demonstrated previously on H526D, H526R and L533P mutations. 24 , 25 For the 10 discordant isolates, and using sequencing as the reference, the LPA misclassified five isolates for Rif resistance profiling versus 2 on the RT MTB RIF/INH assay. The LPA, therefore, missed three additional Rif resistant isolates as compared to the RT MTB RIF/INH assay.…”
Section: Discussionmentioning
confidence: 99%
“…The mycobacterial laboratory of the hospital stores aliquots of remaining decontaminated samples and a specificity of 99%. In addition, Abbott RealTime MTB has been used in several studies [8][9][10], showing a sensitivity of around 80%. Another study comparing both methods found equivalent results [11].…”
Section: Methodsmentioning
confidence: 99%